Impact Green Finance, Profitability, and Capital Structure on Company Value in Mining Sector Companies Listed on the IDX 2019-2023 Period - Sekar Arum Handayani; Pradana Jati Kusuma (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to evaluate the influence of Green Finance, Profitability, and Capital Structure on Firm Value in the mining sector listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2023. The research is motivated by the growing importance of sustainability and financial management strategies in enhancing corporate competitiveness in an increasingly globalized market. A quantitative approach was employed using multiple linear regression analysis, with 22 companies selected through purposive sampling. The findings indicate that, simultaneously, the three independent variables have a significant effect on firm value. Individually, Green Finance and Capital Structure have a positive and significant influence, while Profitability does not show a significant impact. Capital Structure is found to be the most dominant factor affecting firm value, followed by Green Finance. This suggests that companies with sound capital management and strong commitment to sustainability practices are more valued by the market. This research contributes to both theoretical and practical perspectives in financial management, particularly in understanding how financing strategies and sustainability efforts influence market valuation. The findings also recommend that mining companies strengthen their integration of ESG principles and enhance financial efficiency to support long-term value creation and competitiveness